Minimally Invasive Resection of Rare Symptomatic Posterior Mediastinal Mullerian Tumor - Azari, Feredun; Louka, Katie L; Kennedy, Gregory; BS, Elizabeth Bernstein; Babayev, Samir N; Cooper, Kumarasen; Singhal, Sunil (Archives of Clinical and Medical Case Reports, 2021)
Initially reported by Hattori et al. in 2005, there have been recent reports of posterior mediastinal cysts with developmental endosalpingiosis-müllerianosis, also known as Müllerian cysts. Here, we present a unique case of symptomatic posterior mediastinal Müllerian cyst in a 47-year-old female managed with robotic-assisted thoracoscopic surgery. The final diagnosis was confirmed with the histopathologic assessment, which showed the lesion was positive for estrogen, progesterone, PAX8, and WT1 receptors. Mullerian cysts of the posterior mediastinum can cause compressive effects on nearby stellate ganglion, causing symptoms suggestive of the sympathetic storm. These cysts should be evaluated by a dedicated thoracic and gynecologic pathologist for accurate diagnosis. Thoracic surgeons and Gynaecologists should consider these lesions in patients with appropriate clinical and demographic characteristics.